The Rb-related p107 protein can suppress E2F function independently of binding to cyclin A/cdk2. - Smith, E J (1995)
The interaction of the retinoblastoma susceptibility gene product (Rb)-related p107 protein with the E2F transcription factor in S-phase cells facilitates the formation of a multicomponent complex also containing cyclin A and the p33cdk2 kinase. We have created a series of p107 mutants to assess the ability of p107 to inhibit E2F function and the role of the cyclin A/cdk2 complex in this process. We find that p107 mutants that do not bind to E2F also fail to repress E2F-dependent transcription. Moreover, we find that the ability of p107 to suppress E2F-dependent transcription is not dependent on the ability of p107 to associate with cyclin A/cdk2. Finally, an analysis of the ability of the p107 mutant proteins to suppress cell growth suggests that both E2F-dependent and E2F-independent events correlate with this activity.